Students’ Research Efficacy at University Level: Opinion of Teachers and Students in Pakistan (Al-Qamar, 2022)
Research Efficacy is the most important aim that students use to ensure accountability to the public in terms of the value for money invested in the education systems, and to raise educational standards and quality of teaching in university. The major purpose of this study was to investigate the “students’ research efficacy at university Level”. The research was conducted at District Multan. The study focused on determining the relationship between teachers’ and students’ opinion ‘at university level. Researcher used the methodology regarding co-relational research and research tool was developed in questionnaire form with a five-point Likert scale to find results on the basis of findings and conclusion. A total of 120 teachers and 542 students sample was taken from target population After the analysis of data, it was found that there teachers having supervisor’s experiences as 1-5 years with 13 (20.8%), 6-10 years with 44 (36.7%), 11-15 years with 45 (37.5 %) and more than 15 years with 18 (15.0%) were taken as respondents .it was concluded that the frequency of urban, male, public schools, M.Phil./MS teachers having qualification and 11-15 years supervisor’s experiences teachers were greater in number and research efficacy of students as well as   their usage in modifying instruction. It was recommended that institutions concentrate on turning pleasant things into helpful things, such as educational setup research based that promote them as a tool for not just communication and enjoyment but also learning. Future studies should be conducted to identify how teachers use their time on educational research efficacy like schools and colleges levels also. It was concluded from the study that the perception of teachers’ and students for research efficacy at university level was different. It is also recommended that similar study should also be taken for high and higher secondary schools for better perception of research efficacy for both teachers as well as for students.
Keywords: Research Efficacy; University; Teachers; Students; Pakistan